Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells - Yoshihisa Kaizuka; Adam D. Douglass; Rajat Varma; Michael L. Dustin; Ronald D. Vale (2007)
T cells interacting with antigen-presenting cells (APCs) form an "immunological synapse" (IS), a bull's-eye pattern composed of a central supramolecular activation cluster enriched with T cell receptors (TCRs) surrounded by a ring of adhesion molecules (a peripheral supramolecular activation cluster). The mechanism responsible for segregating TCR and adhesion molecules remains poorly understood. Here, we show that immortalized Jurkat T cells interacting with a planar lipid bilayer (mimicking an APC) will form an IS, thereby providing an accessible model system for studying the cell biological processes underlying IS formation. We found that an actin-dependent process caused TCR and adhesion proteins to cluster at the cell periphery, but these molecules appeared to segregate from one another at the earliest stages of microdomain formation. The TCR and adhesion microdomains attached to actin and were carried centripetally by retrograde flow. However, only the TCR microdomains penetrated into the actin-depleted cell center, whereas the adhesion microdomains appeared to be unstable without an underlying actin cytoskeleton. Our results reveal that TCR and adhesion molecules spatially partition from one another well before the formation of a mature IS and that differential actin interactions help to shape and maintain the final bull's-eye pattern of the IS.